2001
DOI: 10.1021/jf0012547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Temperature on the Formation of Volatile Compounds in Cysteine/Reducing Sugar/Starch Mixtures during Extrusion Cooking

Abstract: Mixtures of cysteine, reducing sugar (xylose or glucose), and starch were extrusion cooked using feed pH values of 5.5, 6.5, and 7.5 and target die temperatures of 120, 150, and 180 degrees C. Volatile compounds were isolated by headspace trapping onto Tenax and analyzed by gas chromatography--mass spectrometry. Eighty and 38 compounds, respectively, were identified from extrudates prepared using glucose and xylose. Amounts of most compounds increased with temperature and pH. Aliphatic sulfur compounds, thioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 29 publications
4
35
0
Order By: Relevance
“…Sugars form many volatile compounds in reactions with amino acids, e.g. glucose forms pyrazines with lysine (Ames et al, 2001), and ribose forms many key sulfur compounds with cysteine, like e.g. : 2-furanmethanethiol, 3-mercapto-2-pentanone, 2-methyl-3-furanthiol, 3-mercapto-2-butanone, bis(2-methyl-3-furyl) disulfide, 2-acetyl-2-thiazoline, 1-mercapto-2-propanone and 3-methyl-3-thiophenethiol (Hofmann & Schieberle, 1995;Cerny & Davidek, 2003).…”
mentioning
confidence: 99%
“…Sugars form many volatile compounds in reactions with amino acids, e.g. glucose forms pyrazines with lysine (Ames et al, 2001), and ribose forms many key sulfur compounds with cysteine, like e.g. : 2-furanmethanethiol, 3-mercapto-2-pentanone, 2-methyl-3-furanthiol, 3-mercapto-2-butanone, bis(2-methyl-3-furyl) disulfide, 2-acetyl-2-thiazoline, 1-mercapto-2-propanone and 3-methyl-3-thiophenethiol (Hofmann & Schieberle, 1995;Cerny & Davidek, 2003).…”
mentioning
confidence: 99%
“…They are the predominant flavor component of beef as formation of the Maillard products such as pyrazines and their interaction products are limited (Bredie et al, 1998; Ames et al, 2001). The present study also revealed that aldehydes were the most predominant among the detected flavor compounds in both numbers and amounts in cooked Hanwoo beef.…”
Section: Resultsmentioning
confidence: 99%
“…The types and concentrations of free amino acids/peptides, fatty acids, reducing sugars in foods influence flavor traits as a consequence of their participation in the reactions, oxidation and degradation processes during heating to form flavor components (Macleod, 1994; Mottram, 1994; Elmore et al, 2002). In addition, moisture content, pH, and heating conditions affect types and concentrations of volatile flavor components (Shi and Ho, 1994; Madruga and Mottram, 1995; Ames et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The content of volatile compounds is also affected by pH value and the method of preparation and thermal processing (Meynier and Mottram, 1995;Mottram, 1998;Ames et al, 2001).…”
Section: (Z)-limonene Oxide and (E)-limonene Oxide (Both With Less Dementioning
confidence: 99%
“…It should be noted that the differences between various types of meat are not necessarily always the same, since the composition of volatile compounds is also affected by the degree of meat maturity (Campbell et al, 2001, Stetzer et al, 2008, as well as a number of other genetic and non-genetic factors (Tai and Ho, 1998;Ames et al, 2001;Campbell et al, 2001;Insausti et al, 2005;Calkins and Hodgen, 2007;Cerny and Briffod, 2007). Moreover, the importance of reproducibility of chromatographic analysis, including column and SPME fibre wear, for the reliability of results should be emphasised (own observations).…”
Section: Volatile Aroma Compounds In Raw Meat -Authors' Studiesmentioning
confidence: 99%